This rake of mine eaudiobook - Boyle, Elizabeth (Bachelor Chronicles, 2020)
When the rakehell Lord Jack Tremont kissed Miranda Mabberly, mistaking her for his mistress, neither realized his reckless act would cost Miranda her reputation, her fiancé, and her future. But for Jack, it was a kiss that would haunt—an intoxicating memory of a woman lost to him forever. Years later, hiding incognito far from London—a teacher at Miss Emery's Establishment for the Education of Genteel Ladies—Miranda has made a respectable life for herself, away from the ton and the dangerous men who inhabit it. When a penniless, much humbled, though still damnably attractive Jack arrives at the school to escort a rebellious young niece home, Miranda does her best to avoid the rogue only to end up tumbling into his arms—and reawakening a desire that is anything but proper. She might want to deny her heart, but Miranda's resolve is no match for a trio of schoolgirl matchmakers who knows true passion when they spy it. Now they won't rest until their all-too-proper teacher and the reprobate lord discover the love that is their destiny.